Does Board of Directors Independence Behave Opportunistically or Ethically? Study Corporation Social Responsibility and Earning Management in Indonesia - Muhammad Taufik; Gideon Benhans (Magister Akuntansi Universitas Pancasila, 2021)
ABSTRACT This paper explores the opportunistic issues of EM and ethical issues of CSR where we aim to examine the relationship between CSR and EM and involve the role of BOD independence. Investigation of the relationship using corporate social performance theory where the research sample is a company that publishes sustainability reporting - GRI index for the period 2016 to 2019 in Indonesia. CSR does not affect EM, on the contrary, BOD independence has a positive and significant effect on EM. That is, BOD independence behaves opportunistically. Another finding is that BOD independence does not strengthen or weaken the relationship between CSR and EM. Therefore, despite being opportunistic, BOD independence does not use CSR as a reflection of ethical values to cover EM practices. This paper contributes to showing that BOD independence has 2 characters, namely opportunist on the one hand and ethical on the other.